Histopathological Findings in Corresponding Salpingectomy Specimens of Various Ovarian Neoplasms - Ayesha Imtiaz Malik, Syed Hyder Raza, Seema Butt, Farheen Zehra, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: The aim of this study is to evaluate salpingectomy specimens of all types of ovarian tumors by opting SEE-FIM grossing protocol. Methods: A total of 79 samples of fallopian tubes were grossed following SEE-FIM protocol, as mentioned by CAP. This study was conducted in Pathology department at Niazi Medical and Dental College Sargodha. Results: One third ovarian tumors (n = 26, 33.8%) were bilateral and two fifth tumors (n = 31, 40.3%) were on the right side. More than ninety percent samples (n = 71, 92.2%) had non-precursor lesions. Lastly, most common cases of ovarian tumors were of mature cystic teratoma (n = 16, 20.8%), dysgerminoma (n = 13, 16.9%) and mucinous cystadenoma (n = 12, 15.6%). The results of chi-square tests showed significant association of both histopathological changes in fallopian tube (χ2 (6) = 31.05, p < .001) and histopathological findings (χ2 (2) = 7.81, p < .05) with types of ovarian neoplasm. Conclusion: The routine following of SEE-FIM is an easily adoptable and valuable protocol in terms of finding unexpected / incidental lesions and their correlation with different ovarian neoplasms. Keyword: SEE-FIM protocol, Salpingectomy specimen, precursor fallopian tube lesions.